Robert Guthrie and the Trials and Tribulations of Newborn Screening - Harvey L. Levy (MDPI AG, 2021)
Routine newborn screening for many disorders is now so ingrained in newborn care that there is no question about whether it should be done. However, acceptance of newborn screening was not guaranteed when Robert Guthrie introduced it for phenylketonuria (PKU). This article describes the professional and personal story of Guthrie, a physician and microbiologist, who veered from cancer research to a commitment to prevent intellectual disability from PKU. It recounts how Guthrie was able to overcome strong opposition to mandatory screening from prominent physicians and medical societies, so that newborn screening for PKU would be routinely performed throughout the developed world, and would eventually form the basis for the (much more) comprehensive screening conducted today.